Sensitivity to high salinity in tetraploid citrus seedlings increases with water availability and correlates with expression of candidate genes - Mouhaya, Waffa; Allario, Thierry; Brumos, Javier; Andres, Fernando; Froelicher, Yann; Luro, Francois; Talón, Manuel; Ollitrault, Patrick; Morillon, Raphael (2017)
We investigated tolerance to high salinity in well-irrigated diploid and tetraploid citrus. Comparisons were made between two diploids (2x) of trifoliate orange (Poncirus trifoliata (L.) Raf.) and willow leaf mandarin (Citrus deliciosa Ten), their respective doubled diploids (4x) and the allotetraploid (FLHORAG1) obtained from the protoplast fusion of trifoliate orange and Willow leaf mandarin. Salinity stress was applied by progressively increasing the concentration of NaCl from 50 mM to 400 mM for 8 weeks. Two-year-old plants were watered daily. Maximum quantum yield of PSII, and leaf and root chloride and sodium content were monitored. We previously reported that under moderate saline stress, citrus 4x genotypes were more tolerant that the 2x, but under these experimental conditions, 4x seedlings were certainly more sensitive to salt stress than 2x, as they accumulated more toxic ions and were more affected than 2x. Chloride accumulation in 4x leaves was greater and the maximum quantum yield of PSII was more reduced in 4x than in 2x. The expression of several candidate genes involved in signal transduction, sodium and chloride transport, osmotic adjustment, regulation of the stomata opening and detoxification processes were also investigated by quantitative real-time reverse transcription-PCR. A high correlation was observed between phenotype of sensitivity to stress and gene expression changes.